Answer:
D. is correct!
Step-by-step explanation:
ht tps://us-static.z-dn.net/fil es/ded/302e17a93f9f7dceb0b9635c302342ae.jp g
^ just an example
brainliest?
Answer:
corresponding
Step-by-step explanation:
If these triangles are congruent, then side RS is congruent to side TV and that means that y = 4 - x. If y = 4-x, we can sub that into the next equation where side RV = side ST and 1 = 4x - y. If y = 4-x, we sub in accordingly to get 1 =4x - (4 - x). That simplifies to 1 = 4x - 4 + x which is, combining like terms, 5 = 5x. That means that x = 1. If x = 1, and y = 4 - x, then y = 4 - 1 and y = 3. There you go!
Answer:
see explanation
Step-by-step explanation:
x² + 3x + 7 = 5 ( subtract 5 from both sides )
x² + 3x + 2 = 0 ← in standard form
(x + 2)(x + 1) = 0 ← in factored form
Equate each factor to zero and solve for x ( zero product rule )
x + 2 = 0 → x = - 2
x + 1 = 0 ⇒ x = - 1
--------------------------------------------------------------
x² - 2 = - 2x² + 5x ( subtract - 2x² + 5x from both sides )
3x² - 5x - 2 = 0 ← in standard form
(3x + 1)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
3x + 1 = 0 ⇒ 3x = - 1 ⇒ x = - ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
x - 2 = 0 ⇒ x = 2
------------------------------------------------------------
(x + 3)² + 4x = 0 ← expand left side using FOIL and simplify
x² + 6x + 9 + 4x = 0
x² + 10x + 9 = 0 ← in standard form
(x + 9)(x + 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 9 = 0 ⇒ x = - 9
x + 1 = 0 ⇒ x = - 1